A tale of two shocks in SN 2004dj. Issue Volume 9:Issue S296(2013) (29th January 2014) - Ray, Alak; Chakraborti, Sayan; Yadav, Naveen; Smith, Randall; Chandra, Poonam; Pooley, David
Abstract: Type IIP SNe constitute a major fraction of all core-collapse supernovae and arise from massive stars that end their lives close to Red Supergiants. The blastwave from the SN interacting with the progenitor's circumstellar matter produces a hot region bounded by a forward and a reverse shock from which most of the X-ray emission originates. Analysis of archival Chandra observations of SN 2004dj, one of the nearest supernovae since SN 1987A, together with published data from radio and optical bands determines the pre-explosion mass-loss rate, blastwave speed, electron acceleration and magnetic field amplification efficiencies. X-ray emission arises from both inverse Compton scattering by non-thermal electrons accelerated in the forward shock and from thermal emission from the supernova ejecta hit by the reverse shock. Determination of the properties of the radiating plasma based on the separation of thermal and non-thermal radiation differentiates different types of supernovae and their environments.